Peran Supervisi Klinis dalam Peningkatan Kualitas Pembelajaran - Azila Azila; Nurzakiya Nurzakiya; Marseli Widea Putri (Asosiasi Periset Bahasa Sastra Indonesia, 2025)
Clinical supervision is a strategic approach in improving the quality of learning through mentoring and teacher training in a planned, focused and sustainable manner. This approach communicates collaboration between supervisors and teachers in analyzing and improving learning practices in the classroom. This article discusses the role of clinical supervision in identifying teachers' professional needs, providing constructive feedback, and supporting the development of relevant pedagogical skills. The research results show that the implementation of effective clinical supervision can increase teacher competence, improve teaching methods, and create a more optimal learning environment for students. Additionally, clinical supervision also encourages a culture of reflection and continuous learning.